2008
DOI: 10.1117/1.2992139
|View full text |Cite
|
Sign up to set email alerts
|

Model-based spectroscopic analysis of the oral cavity: impact of anatomy

Abstract: In order to evaluate the impact of anatomy on the spectral properties of oral tissue, we used reflectance and fluorescence spectroscopy to characterize nine different anatomic sites. All spectra were collected in vivo from healthy oral mucosa. We analyzed 710 spectra collected from the oral cavity of 79 healthy volunteers. From the spectra, we extracted spectral parameters related to the morphological and biochemical properties of the tissue. The parameter distributions for the nine sites were compared, and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 35 publications
1
50
0
Order By: Relevance
“…On the other hand, our finding is consistent with previous study carried out by McGee et al [17]. They examined the total hemoglobin variations in all possible anatomical parts of the oral cavity.…”
Section: Discussionsupporting
confidence: 95%
“…On the other hand, our finding is consistent with previous study carried out by McGee et al [17]. They examined the total hemoglobin variations in all possible anatomical parts of the oral cavity.…”
Section: Discussionsupporting
confidence: 95%
“…It is known that subsites in the oral cavity have distinct origins, and consequently distinct anatomical and molecular features. 29,30 Previous°uorescence 31 and re°ectance spectroscopy 32,33 studies have demonstrated de¯-nite spectral contrasts between di®erent subsites in healthy populations. Three major RS studies in thē nger-print and high wavenumber region have also demonstrated di®erences arising due to epithelial and sub-epithelial structures, submucosa and degree of keratinization in subsites of healthy subjects and suggested clustering of sites based on anatomical and spectral similarities.…”
Section: Introductionmentioning
confidence: 99%
“…5. The μ s ' of the lamina propria were similar to the values of buccal mucosa reported in [3], while the μ s ' of the epithelium could not be compared because a single-layer tissue model was used in [3]. The best-fit results of μ a of the epithelium and lamina propria were shown in Fig.…”
Section: Discussionmentioning
confidence: 57%